ANALYSIS OF POVERTY CHARACTERISTICS IN TORETE VILLAGE, BUNGKU PESISIR, MOROWALI REGENCY - Mahamidi, Widyawati; Lutfi, Muthar; Taqwa, Edhi; Yunus, Santi; Yunus, Rita (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
This study aims to analyze the vulnerability profile and economic resilience strategies of poor households, particularly those dominated by the elderly and those with low education levels, in Torete Village. A mixed-methods approach was used. The quantitative study results indicate that the majority of respondents are aged 61 years and above (64.3%), with a basic education level (78.6% are elementary school graduates), and are predominantly housewives (46.4%) or farmers (39.3%). Household expenditure patterns are very conservative, with the majority of respondents (75.0%) having no transportation expenses and focusing their expenditures entirely on basic food needs. This group's economic resilience is supported by high home ownership (96.4%) and the elimination of rent. Qualitative findings confirm that the biggest obstacles faced by respondents are internal factors such as old age and health conditions that limit their ability to earn a productive living. The main strategy used to cover the deficit in needs is relying on financial support from children. In addition, structural issues such as land access and demands for transparency in the distribution of social assistance are also highlighted as significant obstacles to escaping poverty. This study concludes that social assistance needs to be complemented by empowerment programs that target the productive generation in poor families and adequate social protection guarantees for the elderly.